Comparative analysis of different PWM techniques on three-phase voltage source inverter fed induction motor drive - Mahbub, Mohiuddin (Brac University, 2021)
This thesis is submitted in partial fulfilment of the requirements for the degree of Master of Science in Electrical and Electronic Engineering, 2020.